The Influence of Work Morale, Work Environment and Self-Efficacy on the Performance of Balangan Regency Library and Archives Service Employees - Kadir, Abdul; Zulaiha, Yusifa; Leki, Rofinus; Cristine, Marya Yully; Naimah, Naimah (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2024)
This research aims to determine and analyze the influence simultaneously and partially of Work Morale, Work Environment and Self-Efficacy on the Performance of Balangan Regency Library and Archives Service employees. This type of research uses descriptive quantitative with a survey approach where questionnaires will be distributed to all research respondents, where the population in this research is the Balangan Regency Library and Archives Service Employees totaling 230. Determining the number of samples used in the author's research uses the Slovin formula, namely 70 Service Employees Balangan Regency Library and Archives. Data collection techniques use questionnaires and interviews. The measurement scale uses a Likert scale with a preference level of 1 to 5. Data analysis uses multiple linear regression analysis. The test results show that simultaneously and partially Work Morale, Work Environment and Self-Efficacy have a significant effect on the Performance of Balangan Regency Library and Archives Service Employees. The work environment has a dominant influence on the performance of Balangan Regency Library and Archives Service employees.